Climate Change and Infectious Diseases: Global & Bangladesh perspective - Alam, ABMM (Journal of Shaheed Suhrawardy Medical College, 2012)
J Shaheed Suhrawardy Med Coll, 2011; 3 (1): 1-2 DOI: http://dx.doi.org/10.3329/jssmc.v3i1.12051